2003
DOI: 10.1136/ard.62.11.1049
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of inflammation by Doppler ultrasound: quantitative changes after intra-articular treatment in rheumatoid arthritis

Abstract: Objective: To evaluate the use of ultrasound, including quantitative Doppler analysis of synovial vascularisation, before and after intra-articular treatment with glucocorticosteroids in patients with rheumatoid arthritis (RA). Methods: 51 patients with RA were followed prospectively after an intra-articular glucocorticosteroid injection. Disease modifying antirheumatic drug treatment was kept unchanged and no further injections given in this observation period. At baseline, disease activity was estimated clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(85 citation statements)
references
References 24 publications
7
72
1
5
Order By: Relevance
“…In keeping with our results, other studies have found changes in color Doppler or PDUS to be associated with clinical and laboratory response to intraarticular corticosteroid injections (22,33,36), systemic corticosteroid therapy (30,32), and biologic agents (15,31,34,37) in chronic inflammatory arthritis. However, the sensitivity to change of any method should be demonstrated by calculating the intraobserver variation and the SDD between repeated measurements (50).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In keeping with our results, other studies have found changes in color Doppler or PDUS to be associated with clinical and laboratory response to intraarticular corticosteroid injections (22,33,36), systemic corticosteroid therapy (30,32), and biologic agents (15,31,34,37) in chronic inflammatory arthritis. However, the sensitivity to change of any method should be demonstrated by calculating the intraobserver variation and the SDD between repeated measurements (50).…”
Section: Discussionsupporting
confidence: 79%
“…Some different methods have been used for assessing color Doppler or power Doppler findings such as semiquantitative signal scoring (15,22,30,36,37), color pixel counting (31)(32)(33)(34)(35), and resistive index calculating (33,34). We considered semiquantitative signal grading as the most suitable for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler US, in which moving blood cells generate the signal, can be used to detect (8,19,20) and potentially quantify (17,21) the increased synovial blood flow that occurs during joint inflammation. In knee and hip joints, the power Doppler signal has been found to correlate well with the histologic assessment of synovial membrane microvascular density (7,9).…”
Section: Us Methods For Assessment Of Joint Inflammationmentioning
confidence: 99%
“…All images of tendons were obtained under weight-bearing conditions. After completely clipping and then removing the hair on the palmar aspect of the mid-metacarpal region on 10 injured forelimbs using depilatory cream, 7 different regions from the proximal end (bottom of accessory carpal bone) to the distal end (top of the proximal sesamoid bone) of the SDFT (1A-B, 2A-B and 3A-C) were scanned as previously described [6,8], with some modifications using a mobile ultrasound system (iU22, Philips Medical Systems Corporation, Tokyo, Japan). Transverse GS images were recorded at 70 regions in the 10 tendons to determine cross-sectional area (CSA) of the outlined SDFT and cross-sectional hypoechogenic area (CSHA) of the outlined lesion (Table 1).…”
mentioning
confidence: 99%